The association between nutrient patterns and hospital stay duration and symptoms in COVID-19 in Iranian patients: cross-sectional study - Atieh Mirzababaei; Atieh Mirzababaei; Farideh Shiraseb; Azam Mohamadi; Azam Mohamadi; Mahya Mehri Hajmir; Sara Ebrahimi; Zeinab Zarrinvafa; Elham Kazemian; Amir Mehrvar; Khadijeh Mirzaei (Frontiers in Nutrition)
BackgroundAn excessively reactive immune system results in the cytokine storm COVID-19. A healthy diet is essential to maintain the balance between the immune system and inflammatory and oxidative stress. Associations between single foods and nutrients and COVID-19 have been examined. However, no prior study has examined associations between nutrient patterns and COVID-19. This study assessed the link between nutrient patterns and the COVID-19 severity and length of hospital stay in Iranian adults.MethodsThis cross-sectional study included 107 Iranian adults aged 20–60 years, who were admitted to Amir Alam Hospital in Tehran, Iran, due to COVID-19. Data on their symptoms were collected through a demographic questionnaire and verified against their hospital records. Three non-consecutive 24-h dietary recalls were used to collect participants’ food and beverage intake. Principal component analysis (PCA) was used to derive nutrient patterns.ResultA total of 95 Covid patients with a mean age of 46.2 years were included. Four major dietary patterns were identified using the Scree Plot chart, including high carbohydrate and high minerals pattern; high protein and high vitamins pattern; high fat pattern; and poor nutrient pattern. Adherence to the poor nutrient patterns was associated with a higher number of hospitalization days and lower appetite (p < 0.05). The poor dietary patterns were associated with an increased likelihood of headache, fever, and respiratory distress syndrome (RDS). Also, headaches were more common with adherence to the high-fat pattern (p < 0.05).ConclusionThe findings of this study show that a poor nutrient pattern is related to longer hospital stays and reduced appetite. It also connected to an increased likelihood of symptoms including headaches, fever, and respiratory distress syndrome. A strong association was found between respiratory distress syndrome, headaches, and a high-fat diet was found. Further studies with prospective designs are needed to better understand and validate these findings.